Ectopic over-expression of the maize β-glucosidase Zm-p60.1 as a molecular tool to probe subcellular compartmentation of cytokinin metabolism - Kiran, Nagavalli Subbanna, 1972- (2005)
This thesis deals with the subcellular compartmentation of cytokinin metabolism, specifically with the detailed characterization of the response of transgenic tobacco over-expressing the maize beta-glucosidase Zm-p60.1 in response to exogenous zeatin. Analyses were performed on two subcellular variants a) the wild-type enzyme where the enzyme is localised in the chloroplast and b) a recombinant version that is retargeted to the vacuole. The results obtained during the work on this thesis served to characterise the use of Zm-p60.1 as a powerful molecular tool to elucidate the complex network of regulation that underlies the subcellular compartmentation of cytokinin metabolism.